Clothing in Islam: Religious Prescription, Identity Expression, and Sociopolitical Issue - Nadjia , KESSAS; Ahmed , OUNANE (Journal of Ecohumanism, 2024)
This study offers an in-depth reflection on women’s dress in Islam by exploring its biblical origins, theological foundations, and its diverse cultural and geographical expressions. It also examines contemporary issues related to the visibility of the Hijab and Niqab in both Muslim and Western societies. When it comes to the veil in the Qur’an, it is not a new topic. In fact, if we trace it throughout history, we find it present not only in sacred texts but also in various ancient civilizations, where it was common and even considered normal. According to their beliefs, this manner of dress served as protection against envy. Even men participated in this practice, as many recognized civilizations adopted similar garments. This tradition was often associated with symbolic or sometimes spiritual purposes.